Comparative survival and growth performance of European lobster larvae, Homarus gammarus, reared on dry feed and conspecifics. (21st April 2017) - Powell, Adam; Hinchcliffe, James; Sundell, Kristina; Carlsson, Nils‐Gunnar; Eriksson, Susanne P.
Abstract: A bottleneck of crustacean larval culture concerns nutrition and associated cannibalism in communal rearing systems, which impact on larval survival, development and growth. For early‐stage European lobster, Homarus gammarus larvae, feeding ecology and body composition are largely unknown. We initiated four progressive feeding experiments (novel feed types, feeding regime and feed size and cannibalism effects) on growth and survival, to inform and update husbandry protocols. Performance of larvae offered a dry commercial feed was not significantly different compared with a conventional wet plankton feed of the same ration and size grade (both within 600–1, 000 μm). Further experiments found that the same ration of dry feed offered six times daily improved development and growth, over the conventional regime of three times daily. Small‐grade dry feed (particles: 250–360 μm) improved larval performance compared with a larger feed (360–650 μm). Larvae were also fed different proportions of dry feed and/or conspecifics in both communal and individual rearing systems (the latter preventing cannibalism via segregation). Individually reared larvae, fed only dead conspecifics, displayed the greatest survival (80%) to postlarvae. This underlines the impact of cannibalism on survival and nutrition in H. gammarus larviculture. A final experiment analysed H. gammarus zoea 1 composition, identifying deficiencies in ash and carbohydrate in lobster feeds. This suggests a need for a species‐specific, formulated dry feed for H. gammarus larviculture. Our research represents the first investigation of H. gammarus larval composition and dietary requirements and highlights decreased growth potential associated with providing nutrition solely from generic commercial feed.